2007
DOI: 10.1007/s11605-007-0195-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results (6–10 Years) of Laparoscopic Fundoplication

Abstract: Most papers report excellent results of laparoscopic fundoplication but with relatively short follow-up. Only few studies have a follow-up longer than 5 years. We prospectively collected data of 399 consecutive patients with gastroesophageal reflux disease (GERD) or large paraesophageal/mixed hiatal hernia who underwent laparoscopic fundoplication between January 1992 and June 2005. Preoperative workup included symptoms questionnaire, videoesophagogram, upper endoscopy, manometry, and pH-metry. Postoperative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 29 publications
1
26
0
4
Order By: Relevance
“…8 Numerous studies have shown that patients with ERD or BE are effectively treated by antireflux surgery, with safe, long-term control of reflux symptoms, normalization of esophageal acid and nonacid exposure, and a significant improvement in quality of life. [10][11][12][13][14] Few data, in contrast, are available on the results of surgical therapy for all stages of the GERD spectrum including NERD. 13,15 The results of surgical treatment are especially important for patients with NERD as medical treatments are widely reported as being less effective for these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Numerous studies have shown that patients with ERD or BE are effectively treated by antireflux surgery, with safe, long-term control of reflux symptoms, normalization of esophageal acid and nonacid exposure, and a significant improvement in quality of life. [10][11][12][13][14] Few data, in contrast, are available on the results of surgical therapy for all stages of the GERD spectrum including NERD. 13,15 The results of surgical treatment are especially important for patients with NERD as medical treatments are widely reported as being less effective for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] Few data, in contrast, are available on the results of surgical therapy for all stages of the GERD spectrum including NERD. 13,15 The results of surgical treatment are especially important for patients with NERD as medical treatments are widely reported as being less effective for these patients. [16][17][18] In this study, we investigated the influence of the endoscopically defined GERD stage on the outcome of laparoscopic Nissen fundoplication.…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic fundoplication is a good option to treat gastroesophageal reflux disease, with the improvement of symptoms in 80%-90% of patients (15,31,32) . In almost all patients, dysphagia is a post-treatment complication that lasts for about 6 weeks and then disappears, while in some, the complication persist beyond 6 weeks (4,31) .…”
Section: Introductionmentioning
confidence: 99%
“…Связано это с несколькими факторами. При проведении операций по поводу ГЭРБ, особенно выполненных по традиционной методике, все еще встречается довольно большое число интра-и по-слеоперационных осложнений, которые, по неко-торым данным, встречаются в 24% случаев [23][24][25][26][27][28][29][30][31]. Так, вероятность возникновения перфорации пи-щевода и желудка достигает 9,1% [26,32], пневмо-торакс встречается в 4-5% наблюдений, даже при проведении робото-ассистированной операции [33,34].…”
unclassified
“…Причем длительный прием этих препаратов необходим 5,8-62% опери-рованных пациентов [28,31,41,42,44,45,55,56]. Большинство исследований указывают на необхо-димость приема препаратов, снижающих кислот-ность у 20% оперированных пациентов, однако в одном рандоминизированном контролируемом ис-следовании авторы сообщили о возникновении не-обходимости приема этих препаратов у 62% опери-рованных пациентов [56].…”
unclassified